Diffusion-weighted MR Imaging Offers No Advantage over Routine Noncontrast MR Imaging in the Detection of Vertebral Metastases - Castillo, Mauricio; Arbelaez, Andres; Smith, J. Keith; Fisher, Laurie L. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Diffusion-weighted MR imaging of the spine has been used to differentiate benign from pathologic vertebral body compression fractures. We sought to determine the utility of diffusion-weighted MR imaging in the detection of vertebral metastases and to compare it with conventional noncontrast T1- and T2-weighted MR imaging.METHODS: Fifteen patients with metastases to the spine were studied using conventional MR imaging and diffusion-weighted imaging. Blinded review of all images was undertaken, and patients were categorized according to whether they had focal or multiple lesions. The signal intensity of the lesions was compared on T1-, T2- (fast spin-echo), and diffusion-weighted images.RESULTS: In five patients with focal disease, metastases were hypointense on T1-weighted images; hypointense (n = 2), isointense (n = 1), or hyperintense (n = 2) on T2-weighted images; and hypointense (n = 3) or hyperintense (n = 2) on diffusion-weighted images with respect to presumed normal bone marrow. In 10 patients with disease in multiple sites, all lesions were hypointense on T1-weighted images; hypointense (n = 2), isointense (n = 4), hyperintense (n = 2), or mixed (n = 2) on T2-weighted images; and hypointense (n = 5), hyperintense (n = 3), or mixed (n = 2) on diffusion-weighted images with respect to presumed normal bone marrow.CONCLUSION: As used in this study, diffusion-weighted MR imaging of the spine showed no advantage in the detection and characterization of vertebral metastases as compared with noncontrast T1-weighted imaging, but was considered superior to T2-weighted imaging.